Measuring Technology and Mechatronics Automation in Electrical Engineering - Hou, Zhixiang; SpringerLink (Online service) (Boston, MA : Springer US, 2012)
Measuring Technology and Mechatronics Automation in Electrical Engineering includes select presentations on measuring technology and mechatronics automation related to electrical engineering, originally presented during the International Conference on Measuring Technology and Mechanatronics Automation (ICMTMA2012). This Fourth ICMTMA, held at Sanya, China, offered a prestigious, international forum for scientists, engineers, and educators to present the state of the art of measuring technology and mechatronics automation research.
Adoption of Mobile Content Service in 3G Era: An Empirical Analysis in China -- A Game Analysis on Multi-level Emergency Management for Construction Accident -- Agent-based Modeling of Water Bloom Mechanism in Reservoirs -- A Hardware-in-the-Loop System for Development of Automotive Battery Management System -- A Master-Slave System for Intelligent Visual Surveillance -- A Method of Detection and Tracking for Laser Spot -- Analysis of Starting Process for Medium-sized Induction Motors with High-voltage -- An Epipolar Rectification Algorithm for Uncalibrated Images -- A New Approach for Multi-objective-optimization-based Fuzzy-PID Control -- A New Naive Style Possibilistic Network Classifier -- An Improved Ant Clustering Algorithm Based on Habitation-searching Method -- An Optimal Model of Full Postponement Strategy in a Two-Stage Supply Chain -- Application of an Improved Watershed Algorithm in Craniocerebrum MRI Image -- Application of Data Fusion in Ecological Environment Monitoring System -- A Skew Detection Algorithm for PDF417 in Complex Background -- A Study of Cancelling the Leakage Signal with a RPC for Single Antenna LFMCW Radar Altimeter -- A VCO Nonlinearity Correction Method Based on BP Network -- Blood Skeleton Extraction Approach for Retinopathy Images -- Calculation and Analysis of Temperature and Fluid Fields in Water-Cooled Motor for Coal Cutters -- Combined Genetic Algorithm Control for Bearingless Motor Suspended System -- Corner Detection via Two-Layer Threshold Method -- DC Transformer Based on Two Dual Switches Push-Pull DC Converters -- Design and implementation of Embedded File system cache management -- Differential Evolution Using Second Mutation for High-Dimensional Real-Parameter Optimization -- Dynamic Multi-objective Optimization Algorithm based on GEP and Virus Evolution -- Dynamics Analysis of a Linear Shale Shaker in Considering Forces of Solids -- -fuzzy -ideals in lattice implication algebras -- Face Detection Of Adaboost Fast Training Algorithm Based On Characteristic Reduction -- Fast Haze Removal Algorithm for Surveillance Video -- Genetic Algorithm and fuzzy based Combustion Temperature control Model of MSW Incinerators -- Hardware-in-the-Loop for on-Line Identification of SSP Driving Motor -- Hybrid Adaptive fuzzy vector control for single-phase induction motors -- Hybrid Intelligent Algorithm Based on Hierarchical Encoding for Training of RBF Neural Network -- Improved Fuzzy Neural Network for Stock Market Prediction and Application -- Landslide Recognition in Mountain Image Based on Support Vector Machine -- Magnetic Field Parameter Calculation Of Permanent Magnet Reciprocating Generator -- Modeling and Vibration Control of Piezoelectric Stack Actuator in Adaptive Truss Structure -- Modeling of Human Balance Process and Application in Evaluation -- Monitoring of Winding Deformation of Power Transformer by Using Nanosecond Pulses -- Multi-document Automatic Summarization based on the Hierarchical Topics -- Observer-based Feedback Control for Networked Control Systems with Quantisation and Packet Dropouts -- Optimization and Design of Key Structure for Electric Equipment based on MDO -- Optimized assignment of airport gate configuration based on immune genetic algorithm -- Output Feedback Adaptive Dynamic Surface Control for a Class of Nonlinear Systems with Input Saturation -- PID Tuning of Networked Feedforward-Feedback Control Systems -- Plume Source Localization Based on Multi-AUV System -- Preliminary risk assessment of metal pollution in source water of Huaihe River at Jiangsu Province Section (China) -- Properties Of Degree Induced Covering Rough Set -- Real-time Setting and Processing on LCD Touch Panel for Electronic Handwriting Exercising to Chinese Character -- Research and Construction of a Sensing Forest System based on the Internet of Things -- Research and Simulation of Variable Step-Size Uncorrelated adaptive Volterra filter Algorithm on Anti-vibration and De-noising -- Research of Product Development Chain Modeling Technology Based on Semantic Web -- Research on Cycling Policies in the UK White Paper -- Robot Simultaneous Localization And Mapping Based On Non-Linear Interacting Multiple Model -- Scalable Video Coding Scheme Based On H.264/MPEG-4 MVC -- Study About the Influence on the Numerical Analysis of Pump Restoration Scheme to the Saline Groundwater by Water Sensitivity -- The Antenna Up-to-down Gain Ratio Design for Multipath Mitigation of GNSS Reference Station Receivers -- The Difference Method of 2-Dimensional Euler Equations with Flux Vector Splitting -- The Information Key Technologies for Quality & Safety Monitor and Management of Agricultural Products -- The Research of the Systematical Construction Method of Chinese Conventional Road Guide Signs Based on the Characteristic of Chinese Drivers -- Voltage Sag Detection Algorithm Based on Dual DQ Decoupling Transformation.
Keywords: Engineering; Electronics; Engineering; Control, Robotics, Mechatronics; Measurement Science and Instrumentation; Electronics and Microelectronics, Instrumentation